2014
DOI: 10.4184/asj.2014.8.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Transpedicular Implant Failure: A Clinical and Surgical Challenge and Its Radiological Assessment

Abstract: Study DesignIt is a multicenter, controlled case study review of a big scale of pedicle-screw procedures from January 2000 to June 2010. The outcomes were compared to those with no implant failure.PurposeThe purpose of this study was to review retrospectively the outcome of 100 patients with implant failure in comparison to 100 control-patients, and to study the causes of failure and its prevention.Overview of LiteratureTranspedicular fixation is associated with risks of hardware failure, such as screw/rod bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 29 publications
(58 reference statements)
2
45
0
7
Order By: Relevance
“…In clinical practice, orthopedic and dental implant complications have been reported to be as high as ∼34% and ∼8%, respectively. Of the 34% failure rate in orthopedic procedures, 16% were attributed to screw loosening during the healing period which is believed to be caused by failure to establish primary stability at the time of instrumentation, or lack of osseointegration during the healing period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, orthopedic and dental implant complications have been reported to be as high as ∼34% and ∼8%, respectively. Of the 34% failure rate in orthopedic procedures, 16% were attributed to screw loosening during the healing period which is believed to be caused by failure to establish primary stability at the time of instrumentation, or lack of osseointegration during the healing period.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of osseointegration continues to be a clinical challenge. Eldin et al determined that in a cohort of implant failures related to screw complications in the thoracolumbar, lumbar, or lumbosacral spine, were either due to screw fracture or screw loosening . Additionally, dental implant failure rates have been reported to be as high as ∼8%, due to excessive micromotion at the bone‐implant interface, as well as the inability to achieve functional loading .…”
mentioning
confidence: 99%
“…A recent review showed that approximately 50% of spinal implant failures were attributed to screw complications such as loosening (~16%) and fracture (~34%) (Eldin et al, 2014). In an attempt to prevent these type of failures, several studies have employed the use of hydroxyapatite (HA)-coated titanium alloy implants, since HA acts as a biomimetic material to promote osseointegration.…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the phenomena observed within the fixture threads. Surgical instrumentation promotes initial bone remodeling that takes place in tandem with new bone formation (Coelho and Jimbo, 2014; Eldin et al, 2014). the decrease in BAFO seen at 3 weeks indicates a loss of bone fraction due to remodeling, and the regain of bone fraction observed at 6 weeks can be attributed to the production of woven bone occupying the healing chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the significantly reduced integration of the screws at the screw-bone interface, screw loosening is more common in osteopenia and osteoporotic bones [25]. The previous investigations have demonstrated an incidence of screw loosening of up to 60 % in osteoporotic bones [7] compared to 1-27 % in nonosteoporotic patients treated with rigid posterior stabilization [12,13,24]. Based on this, newer techniques and materials have been developed to prevent this kind of complication [19].…”
Section: Introductionmentioning
confidence: 96%